TFT Backplanes Doped by BF2 Ion for Improved Stability and AMOLED Display Quality - Ying Shen; Fa‐Hsyang Chen; Dongliang Yu; Xue Liu; Yinghai Ma; Xuyang Zhang; Feiyue Cheng; Xiujian Zhu; Xuecheng Zou (Advanced Electronic Materials)
Abstract This study investigates the effects of various ion implantation processes on the electrical performance of flexible low‐temperature polycrystalline silicon (LTPS) thin‐film transistor (TFT) backplanes. The introduction of BF2 ion implantation induces an additional shallow defect level near the valence band edge within the polycrystalline silicon band gap, as confirmed by deep‐level transient spectroscopy (DLTS). Simultaneously, this process reduces deep‐level traps within the band gap. Density functional theory (DFT) calculations further reveal that the BF2 clusters in polycrystalline silicon function as donors, effectively passivating defect states within the TFT channel. This effect contributes to the observed reduction in deep‐level traps. Consequently, BF2‐doped TFT channels exhibit a lower density of deep‐level traps, leading to enhanced electrical stability of the TFT devices under continuous electrical stress. As a result, AMOLED displays driven by these stabilized TFT backplanes demonstrate reduced image sticking and improved image quality. The above achievements provide a systematic methodology that combines experimental analysis and theoretical model calculation for the in‐depth exploration of the intrinsic mechanisms of device performance in the display industry.